The Price of Capital Goods, Investment, and Labor: Micro-Evidence from a Trade Liberalization - Sergii Meleshchuk; Yannick Timmer (CESifo GmbH, 2024)
In this paper, we show that a reduction in capital goods prices induced by trade policies can stimulate both investment and labor. We exploit a quasi-natural experiment in the form of a trade reform in Colombia to study how firms with differential exposure to reductions in capital goods tariffs react in terms of their investment and labor decision. Firms that see a larger decline in the input tariff for capital goods increase investment and labor for production, as well as their labor share. Reductions in input tariffs are passed through to input prices for all goods. However, only lower prices for capital, not for other goods, translate into more investment and employment of production workers.
Keywords: D22; D25; E22; E24; F13; F14; 330; investment; tariffs; capital goods; price of capital; employment; trade reform; Colombia